(untitled) (Journal of Applied Learning and Teaching, 2024)
The debate on online and traditional classroom methods has gained traction in the rapidly changing world of education. This is especially true when discussing elements that are critical to the learning process, such as student motivation and self-confidence. Our research examined these components in great detail in the context of a speaking course to learn German as a foreign language. Thirty-three students made up the sample. They were divided into two groups: one that took part in traditional classroom discussions (which served as the control group) and another that experimented with discussions in the Gather.town online community. The first of our study’s two goals was to determine whether the students’ self-efficacy and intrinsic motivation had changed significantly after six weeks of discussion. Secondly, we were interested in determining which medium—face-to-face or online—had a stronger influence on fostering these essential educational traits. We used surveys that were distributed at the start and end of the six-week study window to gather our findings. The findings of our study were compelling. Compared to their peers in the traditional classroom environment, students who used Gather.town as their discussion platform displayed a more pronounced increase in both motivation and self-efficacy. This highlights the burgeoning potential of online learning environments like Gather.town in the modern educational landscape and suggests the benefits of incorporating such cutting-edge tools to increase student motivation and confidence.